Fabrication of a single sub-micron pore spanning a single crystal (100) diamond membrane and impact on particle translocation. (October 2017) - Webb, Jennifer R.; Martin, Aiden A.; Johnson, Robert P.; Joseph, Maxim B.; Newton, Mark E.; Aharonovich, Igor; Toth, Milos; Macpherson, Julie V.
Abstract: The fabrication of sub-micron pores in single crystal diamond membranes, which span the entirety of the membrane, is described for the first time, and the translocation properties of polymeric particles through the pore investigated. The pores are produced using a combination of laser micromachining to form the membrane and electron beam induced etching to form the pore. Single crystal diamond as the membrane material, has the advantages of chemical stability and durability, does not hydrate and swell, has outstanding electrical properties that facilitate fast, low noise current-time measurements and is optically transparent for combined optical-conductance sensing. The resulting pores are characterized individually using both conductance measurements, employing a microcapillary electrochemical setup, and electron microscopy. Proof-of-concept experiments to sense charged polystyrene particles as they are electrophoretically driven through a single diamond pore are performed, and the impact of this new pore material on particle translocation is explored. These findings reveal the potential of diamond as a platform for pore-based sensing technologies and pave the way for the fabrication of single nanopores which span the entirety of a diamond membrane. Graphical abstract: We demonstrate for the first-time fabrication of a sub-micron pore which spans the entirety of a single crystal diamond membrane and investigate the impact of this new pore material on particle translocation.